Symptom Burden of Atrial Fibrillation and Its Relation to Interventions and Outcome in Europe. Issue 11 (18th May 2018) - Schnabel, Renate B.; Pecen, Ladislav; Rzayeva, Nargiz; Lucerna, Markus; Purmah, Yanish; Ojeda, Francisco M.; De Caterina, Raffaele; Kirchhof, Paulus
Abstract : Background: Little is known about the association of atrial fibrillation symptom burden with quality of life and outcomes. Methods and Results: In the Prevention of Thromboembolic Events–European Registry in Atrial Fibrillation (n=6196 patients with atrial fibrillation; mean±SD age, 71.8±10.4 years; 39.7% women), we assessed European Heart Rhythm Association score symptoms and calculated correlations with the standardized health status questionnaire (EQ‐5D‐5L). Patients were followed up for atrial fibrillation therapies and outcomes (stroke/transient ischemic attack/arterial thromboembolism, coronary events, heart failure, and major bleeding) over 1 year. Most individuals (92%) experienced symptoms. Correlations with health status and quality of life were modest. In multivariable‐adjusted regression models, the dichotomized European Heart Rhythm Association score (intermediate/frequent versus never/occasional symptoms) was associated with cardioversions (odds ratio [OR], 1.21; 95% confidence interval [CI], 1.01–1.45) and catheter ablation (OR, 1.97; 95% CI, 1.44–2.69), and inversely related with heart rate control (OR, 0.80; 95% CI, 0.70–0.92) and heart failure incidence (OR, 1.65; 95% CI, 1.16–2.34). Anxiety was inversely related with stroke/transient ischemic attack/arterial thromboembolism (OR, 0.55; 95% CI, 0.32–0.93), whereas chest pain related positively with coronary events (OR, 2.45; 95% CI, 1.42–4.22). Fatigue (OR, 1.84; 95% CI, 1.30–2.60), dyspnea (OR, 2.33; 95% CI, 1.63–3.33), and anxiety (OR, 1.72; 95% CI, 1.16–2.55) were associated with heart failure incidence. Palpitations were positively associated with cardioversion (OR, 1.32; 95% CI, 1.08–1.61) and ablation therapy (OR, 2.02; 95% CI, 1.48–2.76). Conclusions: A higher symptom burden, in particular palpitations, predicted interventions to restore sinus rhythm. The score itself had limited predictive value, but its individual components were related to different and specific clinical events, and may thus be helpful to target patient management.